Finger Fractures as an Early Manifestation of Primary Hyperparathyroidism Among Young Patients: A Case Report of a 30-Year-Old Male With Recurrent Osteoporotic Fractures. Issue 20 (May 2016) - Ozaki, Akihiko; Tanimoto, Tetsuya; Yamagishi, Eiki; Sato, Shunsuke; Tsukada, Manabu; Sawano, Toyoaki; Leppold, Claire; Tsuda, Kenji; Asakura, Takanori; Tsubokura, Masaharu; Kato, Shigeaki; Kami, Masahiro; et al.
Abstract : Abstract: Osteoporosis and osteoporotic fractures represent a substantial health burden, and predominantly affect the elderly. Younger generations may also develop these conditions because of various predisposing conditions, including primary hyperparathyroidism. However, little information is available regarding early skeletal manifestations of primary hyperparathyroidism. A 30-year-old Japanese male presented with pain in his left wrist, and was diagnosed with a distal radius fracture. During surgery, we noticed decreased bone strength of the fracture site. Further investigation found osteoporosis and primary hyperparathyroidism owing to a solitary parathyroid adenoma, which was resected without significant complications. History revealed that the patient suffered a metacarpal bone fracture of his right fifth bone 6 months earlier. Although serial x-rays at that time had shown rapidly developed cortical bone erosion around the fractured finger, the possibility of primary hyperparathyroidism was overlooked because of poor awareness of the condition, leading to a 6-month delay in the diagnosis of primary hyperparathyroidism. Clinicians should be aware that finger fractures may be an early skeletal manifestation of primary hyperparathyroidism that can help achieve a prompt diagnosis of the condition, especially when they occur in young adults in the absence of major trauma.